Validation and quantitative analysis of cadmium, chromium, copper, nickel, and lead in snake fruit by Inductively Coupled Plasma-Atomic Emission Spectroscopy - M. Tan, Sudjadi, Astuti, Rohman & & (Journal of Applied Pharmaceutical Science, 2018)
Snake fruit or known as Salak is one of the favourite fruits and is consumed not only in Indonesia but also in the worldwide. The fruit may be contaminated with heavy toxic metals such as cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), and lead (Pb). The purpose of this study was to validate inductively coupled plasma-atomic emission spectroscopy (ICP-AES) for determination of Cd, Cr, Cu, Ni, and Pb in snake fruit. ICP-AES was validated by determining several validation parameters which included linearity and range, limit of detection and limit of quantification, precision, and accuracy. The validated method was further used for assay of these metals in snake fruit. The results showed that ICP-AES was linear over the concentration ranges of 0.025–1.0 μg/mL for Cd, Cr, and Ni and 0.050–1.0 μg/mL for Cu and Pb, respectively. The values of coefficient of determination (r2) obtained for these regressions were higher than 0.99. The values of limit of detection (LoD) of Cd, Cr, Cu, Ni, and Pb found were at 0.0010 μg/mL, 0.0024 μg/mL, 0.0047 μg/mL, 0.0037 μg/mL, and 0.0091 μg/mL respectively, while limits of quantitation were of 0.0030 μg/mL (Cd), 0.0073 μg/mL (Cr), 0.0143 μg/mL (Cu), 0.0113 μg/mL (Ni), and 0.0274 μg/ mL (Pb), respectively. The validated method was accurate and precise enough for determination of these heavy metals in snake fruit samples as indicated by acceptable values of recovery and low relative standard deviation (RSD) values. The developed method has been successfully used for determination of Cd, Cr, Cu, Ni, and Pb levels commercially available in the markets and farms.
Keywords: Method validation, snakefruit, ICP-AES, heavymetals.